2016
DOI: 10.21560/spcd.77608
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’de Kadın Göçmenlik ve Göçün Kadın Sağlığı Üzerine Etkisi

Abstract: ÖzSosyal, kültürel ve fiziksel olarak toplumu ve bireyleri etkileyen göç, sağlık ve sağlık değişkenleri üzerinde de çok önemli etkilere sahiptir. Göç süreci bedensel ve zihinsel sağlığı etkiler. Özellikle riskli gruplar içinde kadınlar bu süreçten daha fazla etkilenmektedir. Kadınların sağlık hizmetlerinden tam, eşit ve en yüksek standartlarda faydalanmalarını sağlamak, kadının insan haklarının tam olarak sağlanmasının temel koşullarından biri olmakla beraber göçmen annelerde yeni yaşama uyum, kültürel çevrede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 4 publications
0
3
0
2
Order By: Relevance
“…In addition, the report states that 30,000 of these women are pregnant (15). This situation reveals that female immigrants have different and special protection needs compared to male immigrants (16). Otherwise, migrant women may encounter reproductive health problems due to both their gender and genderbased problems (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the report states that 30,000 of these women are pregnant (15). This situation reveals that female immigrants have different and special protection needs compared to male immigrants (16). Otherwise, migrant women may encounter reproductive health problems due to both their gender and genderbased problems (17).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the migrant women who have been sexually abused do not know their legal rights or do not apply to institutions that can provide support for fear of being deported. Although immigrant women have high reproductive health needs, their access to relevant services and information is limited due to legal, cultural and language barriers (14,16). In the report of the Middle East Strategic Studies Center (ORSAM) titled Impact of Syrian Refugees on Turkey in January 2015, polygamy with Syrian women has become widespread in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted with adolescents, dietary energy intake was calculated as 1837.1± 461.09 kcal/day in men and 1154.5±361.48 kcal/day in women (Gümüş et al, 2011). Daily energy intakes, respectively; It was determined that it was 2473±595.9 kcal in men and 2327±613.2 kcal in women (Yabancı and Pekcan, 2010). When macronutrients were evaluated in the study, daily carbohydrate intake was found to be 216.15±90.64 g/day in men and 194.09±92.08 g/day in women; Daily dietary protein intake was 58.37 ± 26.33 g/day in men and 42.31 ± 13.93 g/day in women; The mean consumption of dietary fat was determined as 67.95±31.08 in men and 56.71±18.71 in women.…”
Section: Distribution Of Variables By Gendermentioning
confidence: 99%
“…Kadınlar eğitim, sağlık, sosyal güvenlik, siyaset, çalışma yaşamı ve sivil toplum kuruluşları gibi sosyal faaliyet alanlarında cinsiyetçilik veya ayrımcılık kaynaklı çeşitli engellerle karşılaşmaktadırlar. Bir yandan iş gücü piyasalarına, gelir getirici faaliyetlere, eğitim ve öğretim imkânlarına ulaşımında zorluklarla karşılaşırken, diğer yandan da toplumsal ve çevresel ağlar ve etkinlikler kurmasında engeller oluşturmaktadır (Arabacı, Hasgül ve Serpen, 2016). Yapılan çalışmada, İranlı Göçmen kadınların dışlanmaya maruz kaldıkları en önemli etkenin dil sorunu olduğu ortaya çıkmıştır.…”
Section: Tartıģma Ve Sonuçunclassified